Depletion of mitoferrins leads to mitochondrial dysfunction and impairment of adipogenic differentiation in 3T3-L1 preadipocytes. (2nd November 2015) - Chen, Y.-C.; Wu, Y.-T.; Wei, Y.-H.
Abstract: Dysregulation of iron homeostasis is a potential risk factor for type 2 diabetes mellitus (T2DM) and insulin resistance. Iron transported into mitochondria by mitoferrins is mainly utilized for the biosynthesis of iron–sulfur clusters, heme, and other cofactors. Recent studies revealed that mitochondrial dysfunction leads to impaired adipogenesis and insulin insensitivity in adipocytes. However, it is unknown whether mitochondrial iron import and iron status affect the biogenesis and function of mitochondria during adipogenic differentiation. In this study, we used double knockdown of mitoferrin 1 and mitoferrin 2 (Mfrn1/2) to investigate the role of mitochondrial iron homeostasis in mitochondrial bioenergetic function and adipogenic differentiation. The results showed that depletion of Mfrn1/2 in 3T3-L1 preadipocytes impaired the biosynthesis of iron–sulfur proteins in mitochondria due to a decrease in mitochondrial iron content. This was associated with a decrease in mitochondrial oxygen consumption rate and intracellular ATP level in adipocytes with Mfrn1/2 knockdown. Remarkably, Mfrn1/2 deficiency reduced the expression of adipogenic genes and lipid production during adipogenic differentiation. Moreover, insulin-induced glucose uptake and Akt phosphorylation at the Ser473 residue were decreased concurrently in adipocytes differentiated from 3T3-L1 preadipocytes after knockdown of Mfrn1/2. These findings suggest that dysregulation of mitochondrial iron metabolism elicited by knockdown of Mfrn1/2 results in mitochondrial dysfunction, which culminates in the compromise of differentiation and insulin insensitivity of adipocytes. This scenario may explain the recent findings that iron deficiency or alterations in iron metabolism are associated with the pathogenesis of T2DM.